2008
DOI: 10.1007/s12275-007-0156-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and signature pattern analysis of Korean clade HIV-1 using nef gene sequences

Abstract: Phylogenetic studies of the HIV-1 gene sequences isolated from Korean patients have suggested that most of Korean isolates belong to the subtype B strain. This study aims to characterize the Korean clade by molecular phylogenetic analysis using all of the Korean nef gene sequences registered in the NCBI GenBank (N=422), in addition to 41 reference strains and 94 foreign isolates. Through phylogenetic analyses, we verified that most of the Korean isolates belonged to the subtype B, where 78.8% are clustered exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Even with the same data set, different analytical methods estimated different dates (Lukashov and Goudsmit, 2002). Using two genes (nef and vif) and two methods (BA and ML) for each gene, we were able to obtain very similar results, may be due to high similarity of the KCB sequences compared to other subtype B sequences (Park et al, 2006(Park et al, , 2008. The Korean clade diversified 8 to 17 years after the emergence of the subtype B.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Even with the same data set, different analytical methods estimated different dates (Lukashov and Goudsmit, 2002). Using two genes (nef and vif) and two methods (BA and ML) for each gene, we were able to obtain very similar results, may be due to high similarity of the KCB sequences compared to other subtype B sequences (Park et al, 2006(Park et al, , 2008. The Korean clade diversified 8 to 17 years after the emergence of the subtype B.…”
mentioning
confidence: 76%
“…The presence of the Korean clade has been supported by further studies based on molecular phylogenetic analyses of pol (Sung et al, 2001), nef (Kang et al, 1998;Lee et al, 2003), env (Kim et al, 1999a(Kim et al, , 1999b, and vif (Park et al, 2006) genes. The Korean clade, a subcluster of HIV-1 subtype B, accounted for more than 60% of all HIV isolated from Koreans and exhibited unique nucleotide and amino acid sequences that distinguished the Korean clade from others (Park et al, 2006(Park et al, , 2008 HIV-1 is classified into three major groups, M, N, and O, and group M is further divided into several subtypes whose regional distribution is well known. Using the most recent common ancestor (MRCA) sequences inferred from known sampling date and assuming a constant rate of evolution, it was suggested that M group was first established around 1931 (Korber et al, 2000).…”
mentioning
confidence: 99%
See 3 more Smart Citations